2023
DOI: 10.3389/fcvm.2023.1094330
|View full text |Cite
|
Sign up to set email alerts
|

Causal association between cardiovascular diseases and erectile dysfunction, a Mendelian randomization study

Abstract: BackgroundCardiovascular diseases (CVD), including coronary heart disease (CHD), heart failure, ischemic heart disease (IHD), and atrial fibrillation, are prevalent in the aged. However, the influence of CVD on ED is less investigated. This study was performed to clarify the causal association between CVD and ED.Materials and methodsGenome-wide association studies (GWAS) datasets targeting CHD, heart failure, IHD, and atrial fibrillation were downloaded to retrieve single nucleotide polymorphisms (SNPs). Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Out of the total, only 62 articles were specifically focused on CHD and MR. Among these, CHD was considered as an outcome factor in 61 articles, while only 1 article treated CHD as an exposure factor 22 . Notably, 2 of the 61 articles employed the reverse MR method 23,24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the total, only 62 articles were specifically focused on CHD and MR. Among these, CHD was considered as an outcome factor in 61 articles, while only 1 article treated CHD as an exposure factor 22 . Notably, 2 of the 61 articles employed the reverse MR method 23,24 .…”
Section: Resultsmentioning
confidence: 99%
“…Among these, CHD was considered as an outcome factor in 61 articles, while only 1 article treated CHD as an exposure factor. 22 Notably, 2 of the 61 articles employed the reverse MR method. 23 , 24 Within the 61 articles, a comprehensive analysis of 47 exposure factors across 8 categories was conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Second, there is also relevant anatomical evidence that in mice with high BMR, the probability of intimal thickening, arteriosclerosis and myocyte degradation is increased, 37 which is an important mechanism of cardiovascular diseases 38 . A recent Mendelian study revealed an association between BMR and various cardiovascular conditions, such as aortic aneurysm, atrial flutter and heart failure 39 . Although our study utilized a different BMR dataset, our findings, consistent with previous one, indicate that high BMR increases the risk of heart failure and AF.…”
Section: Discussionmentioning
confidence: 99%
“…With the ourishing of publicly available large sample Genome-Wide Association Study (GWAS) data, high statistical power can be obtained more e ciently. Previously, Mendelian randomization designs have been used to explore the causal relationship between aspirin use and many diseases, such as Alzheimer's disease [15], colorectal cancer [16,17], lung cancer[18], heart failure [19], erectile dysfunction [20], but have not been applied to study its effect on PCa.…”
Section: Introductionmentioning
confidence: 99%